Problemy z ustalaniem momentu utraty płynności finansowej przez firmę - Wyrobek, Joanna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The paper presents real-life problems with establishing the moment when the a firm loses liquidity. In particular, it discusses the following issues: definition of liquidity, construction of liquidity ratios, predictive power of liquidity ratios (based on the balance sheet). According to the author, the loss of liquidity should be considered in a long-term perspective and should be based on firm's failure to meet at least one of its obligations and its poor financial situation. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 448-457